“My Monster Self”: Violence and Survival in Margaret Atwood’s Moral Disorder - Fakhrshafaie, Nahid; Bahremand, Alireza (Text Matters: A Journal of Literature, Theory and Culture, 2021)
Margaret Atwood’s novels are usually celebrated for their blunt feminism. However, in Moral Disorder—a series of interconnected stories that forms a novel—feminist concerns are replaced with worries about territory and survival. The protagonist is an insider whose sole concern is to survive and to protect her territory. The confrontation between the narrator as the insider and the outsiders does not occur directly but could be inferred by her cruelty toward other characters and her violence against the animals under her care. The present study argues that this cruelty, which abounds in the novel, could be viewed as a substitute for violence against the outsiders. The narrator’s gaze at the Indian boy who entered the protagonist’s territory manifests a garrison mentality. The frequent references to axes in the novel are compared to the use of axes in “Wilderness Tips,” a short story by Atwood in which axes also have a metaphoric significance. The beheading and dismemberment of domestic animals could be the punishment awaiting the intruder. The novel establishes a division between the insider/outsider, here/there, self/other and civilized/barbaric to call for action and awareness about the importance of protecting one’s territory.